Dynamic linear feedback shift registers: a review - Alshaikhli, Imad Fakhri Taha; Eljadi, Firdous (2014)
An improvement in the security of stream cipher is achieved by introducing dynamic polynomial switching in the Linear Feedback Shift Registers. Several researches declared that this introduction enhances the stream cipher's immunity to cryptanalysis. This paper aims to provide a comprehensive survey that summarizes the recent approaches for applying this idea for the purpose of shaping a clear vision of these designs. This vision will assist the development process of new designs.